Unveiling the Synergistic Interaction Between Liposomal Amphotericin B and Colistin - Teixeira-Santos, Rita; Ricardo, Elisabete; Branco, Ricardo J.; Azevedo, Maria M.; Rodrigues, Acácio G.; Pina-Vaz, Cidália (Frontiers in Microbiology, 2016)
Patients with multiple comorbidities are often administered simultaneously or sequentially antifungals and antibacterial agents, without full knowledge of the consequences of drug interactions. Considering the clinical relevance of liposomal amphotericin B (L-AMB), the association between L-AMB and six antibacterial agents was evaluated against four clinical isolates and one type strain of Candida spp. and two clinical isolates and one type strain of Aspergillus fumigatus. In order to evaluate such combined effects, the minimal inhibitory concentration (MIC) of L-AMB was determined in the presence of 0.5-, 1-, 2- and 4-fold peak plasma concentrations of each of the antibacterial drugs. Since the L-AMB/colistin (CST) association was the most synergic, viability assays were performed and the physiological status induced by this association was characterized. In addition, computational molecular dynamic studies were also performed in order to clarify the molecular interaction. The maximum synergistic effect with all antibacterial agents, except CST, was reached at 4-fold the usual peak plasma concentrations, resulting in 2-to 8-fold L-AMB MIC reduction for Candida and 2-to 16-fold for Aspergillus. For CST, the greatest synergism was registered at peak plasma concentration (3 mg/L), with 4-to 8-fold L-AMB MIC reduction for Candida and 16-to 32-fold for Aspergillus. L-AMB at subinhibitory concentration (0.125 mg/L) combined with CST 3 mg/L resulted in: a decrease of fungal cell viability; an increase of cell membrane permeability; an increase of cellular metabolic activity soon after 1h of exposure, which decreased until 24h; and an increase of ROS production up to 24h. From the molecular dynamic studies, AMB and CST molecules shown a propensity to form a stable molecular complex in solution, conferring a recognition and binding added value for membrane intercalation. Our results demonstrate that CST interacts synergistically with L-AMB, forming a stable complex, which promotes the fungicidal activity of L-AMB at low concentration.